Prevalence of musculoskeletal symptoms from online learning during the COVID-19 epidemic: a systematic review and meta-analysis [version 1; peer review: awaiting peer review] - Gotum, Tanawat; Keeratisiroj, Orawan; Jariya, Wutthichai (F1000 research, 2024)
Purpose The objective of this research was to assess the prevalence of musculoskeletal symptoms in online students. Materials and methods A systematic review and meta-analysis were performed by searching the PubMed, Cochrane Library, SCOPUS, Web of Science, ScienceDirect, ProQuest, CINAHL plus with full text, and Wiley InterScience databases. A total of 3,749 studies were identified between January 2020 and December 2023. The Joanna Briggs Tool for studies reporting prevalence was used to assess the quality of studies. Jamovi 2.4 was used in the meta-analysis. Results Sixteen studies were included and used for the meta-analysis. There were 6 studies of high quality, 9 studies of medium quality and 1 study of low quality. The areas with the highest prevalence of musculoskeletal pain were the neck (51%, 95% CI = 36-66%), lower back (51%, 95% CI = 42-59%) and shoulder (36%, 95% CI = 26-47%). Conclusions The shift to online learning during the COVID-19 pandemic has emerged as a potential factor influencing musculoskeletal pain in students. Educational institutions should study the duration of online learning that begins to impact student injury outcomes.